Understanding Non-Cooperative Behavior: Psychological Insights and Transformational Leadership Approaches - Kokkonda, Subrahmaniyam (Digital Repository of Theses, 2025)
Non-cooperative behavior is a major problem in many organizational, social, and economic contexts, impacting teamwork, productivity, and decision-making. This research investigates the psychological underpinnings of non-cooperative behavior, considering cognitive biases, personality, and socio-environmental factors that lead to resistance, conflict, and disengagement. Based on behavioral psychology, game theory, and organizational behavior, the research identifies major drivers of non-cooperation as lack of trust, perceived unfairness, and misaligned incentives. In addition, this research examines the function of transformational leadership in countering noncooperative tendencies and developing a culture of cooperation. Through vision, stimulation, and individualized consideration, transformational leaders can transform behavioral patterns, build trust, and stimulate shared goals. By combining psychological knowledge with leadership approaches, this study suggests a model for understanding and resolving non-cooperative behavior in teams, organizations, and general societal settings. The results provide practical applications for managers, policymakers, and educators in advocating cooperation and collective achievement. Keywords: Non-cooperative behavior, psychological insights, transformational leadership, cognitive biases, trust, collaboration, game theory, organizational behavior, leadership strategies, conflict resolution.